One‐Pot Synthesis of Indoles from Alkynes and Anilines through Palladium‐Catalyzed Double C‐H Activation using O2 as the oxidant. Issue 1 (29th January 2016) - Shi, Dunfa; Guan, Zhipeng; Yao, Xiuwen; Shi, Wei; Chen, Hao
Abstract: A simple and efficient Pd‐catalyzed tandem procedure for the synthesis of β‐cyanoindoles was achieved. Unactivated anilines and cyanoalkynes were employed as the starting materials to go through nucleophilic additions to form the N‐aryl enamine intermediate, and then followed by Pd‐catalyzed double C−H activation to yield the product in one pot. Moderate to good yields were achieved for 19 examples. LiBr was used as the additive to promote the process. Oxygen was used as the sole oxidant, thus high atom efficiency could be achieved. Abstract : A simple and efficient Pd‐catalyzed tandem procedure for the synthesis of β‐cyanoindoles was achieved directly from unactivated anilines and cyanoalkynes. 19 examples with moderate to good yields were achieved. O2 was used as the sole oxidant, resulting high atom efficiency.